Design and Mentoring of Business Units in Supporting the Empowerment of MSMEs at the Koperasi Desa Merah Putih - Fredy Susanto; Muhammad Taali; Sundaru Guntur Wibowo; Lala Hucadinota Ainul Amri amri; Noor Azly Mohammed Ali (SWAGATI : Journal of Community Service, 2026)
This community service activity is designed to deliver targeted mentoring for business units, fostering the empowerment of Micro, Small, and Medium Enterprises (MSMEs) within the Merah Putih Village Cooperative in Hargosari Village, Sine District, Ngawi Regency. Key challenges for partners include constraints in business management, insufficient business model innovation, and underutilization of marketing strategies and cooperative business unit development.The activity implementation method uses a participatory approach, with stages including needs identification, business unit design, training, mentoring, and evaluation. The mentoring activities focused on strengthening the capacity of cooperative managers and MSMEs to design sustainable business models, manage business operations, and develop adaptive marketing strategies. The results of the activity demonstrated that partners understood the concept of business unit design and began implementing a more structured business model. Furthermore, there was an increase in capacity in business management, business decision-making, and collaboration between cooperative members and MSMEs. The mentoring also encouraged the formation of more productive and market-oriented business units. This activity significantly empowers cooperative-based MSMEs and strengthens business units as catalysts for the local economy. Program sustainability depends on ongoing mentoring and synergy among universities, village governments, and business actors.